Hubungan Overcrowded dengan Response Time di ruang IGD RSUD Dr. MOEWARDI - Selvia Aurellia Avanda avanda; Wahyu Rima Agustin; Saelan Saelan (TRIAGE Jurnal Ilmu Keperawatan, 2026)
Overcrowded or congestion in the Emergency Department (ED), refers to a condition in which the high number of patient visits is not proportional to the available capacity and resources in the ED. Overcrowded in the Emergency Department is a problem that can affect the quality and timeliness of patient care. One indicator of service effectiveness in the ED can be observed through the nurses' response time in providing initial treatment for emergency conditions. This study aims to know the relationship between overcrowded and response time in the Emergency Department of Dr. Moewardi Regional General Hospital. This study employed a non-experimental quantitative method with an analytic observational design using a cross-sectional approach. The study population consisted of 65 emergency department nurses, with a sample of 54 respondents selected based on the inclusion and exclusion criteria. Overcrowded was measured using the National Emergency Department Overcrowding Score (NEDOCS) instrument, while response time was measured using a stopwatch and an observation sheet. Data analysis was conducted through univariate and bivariate analyses using the Spearman Rank test. The results showed that the majority of overcrowded conditions were at level 5 (severely overcrowded), accounting for 38.9%, and most nurses' response times were categorized as fast, at 59.3%. The statistical test results indicated a significant relationship between overcrowded and response time, with a p-value of 0.001 and a correlation coefficient of r = 0.429, indicating a moderate correlation strength. It can be concluded that the higher the level of overcrowded, the more likely the nurses' response time in the Emergency Department tends to be slower. Therefore, effective management strategies are recommended to reduce overcrowded in order to maintain the quality of emergency care services.